Correlation Between Ki67 Expression and 18F-FDG PET/CT SUVmax in Patient with Diffuse Large B-cell Lymphoma and Their Application in Therapeutic Effect Evaluation - YANG Ming; FENG Yanlin; LIU Dejun; YU Fengwen; HUANG Kemin; LI Wen; XIAN Weijun; LU Shengnan; WANG Ying (Zhongliu Fangzhi Yanjiu, 2018)
Objective To discuss the correlation between Ki67 expression and 18F-FDG PET/CT SUVmax in patients with diffuse large B-cell lymphoma(DLBLC) and their application in the evaluation of chemotherapy effect. Methods We retrospectively analyzed 18F-FDG PET/CT images of 55 patients initially diagnosed as DLBLC in our hospital, observed the correlation between Ki67 expression and SUVmax, evaluated the chemotherapy effect by 18F-FDG PET/CT scan, and analyzed whether age, gender, SUVmax and Ki67 expression were the independent influence factors of chemotherapy effect. Results SUVmax was positively correlated with Ki67 expression (P < 0.05), but no correlation with chemotherapy effect (P > 0.05); Age, gender, SUVmax and Ki67 were not independent influencing factors of chemotherapy effect (P > 0.05). Conclusion 18F-FDG PET/CT SUVmax could predict the proliferation and invasion of DLBCL cells, but there is no correlation between SUVmax and chemotherapy effect. Age, gender, SUVmax and Ki67 expression are not independent influencing factors of chemotherapy effect.